2022
DOI: 10.3390/membranes12100994
|View full text |Cite
|
Sign up to set email alerts
|

On the Mixed Gas Behavior of Organosilica Membranes Fabricated by Plasma-Enhanced Chemical Vapor Deposition (PECVD)

Abstract: Selective, nanometer-thin organosilica layers created by plasma-enhanced chemical vapor deposition (PECVD) exhibit selective gas permeation behavior. Despite their promising pure gas performance, published data with regard to mixed gas behavior are still severely lacking. This study endeavors to close this gap by investigating the pure and mixed gas behavior depending on temperatures from 0 °C to 60 °C for four gases (helium, methane, carbon dioxide, and nitrogen) and water vapor. For the two permanent gases, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Rubner et al also observed a significant and irreversible drop in permeance for both He and CO 2 when exposed to water vapor, although the ideal He/CO 2 selectivity increases. [104] Overall, the investigated organosilica membrane demonstrates promising mixed gas behavior for separating permanent gases with small kinetic diameters from larger gas molecules. [104] Besides the separation properties of the films deposited by PECVD, Rubner et al also investigated the mitigation of physical aging of ultrathin polymer films with intrinsic microporosity.…”
Section: Experimental Studies Of Membrane Propertiesmentioning
confidence: 89%
See 3 more Smart Citations
“…Rubner et al also observed a significant and irreversible drop in permeance for both He and CO 2 when exposed to water vapor, although the ideal He/CO 2 selectivity increases. [104] Overall, the investigated organosilica membrane demonstrates promising mixed gas behavior for separating permanent gases with small kinetic diameters from larger gas molecules. [104] Besides the separation properties of the films deposited by PECVD, Rubner et al also investigated the mitigation of physical aging of ultrathin polymer films with intrinsic microporosity.…”
Section: Experimental Studies Of Membrane Propertiesmentioning
confidence: 89%
“…Rubner et al also observed a significant and irreversible drop in permeance for both He and CO2 ${\text{CO}}_{2}$ when exposed to water vapor, although the ideal He/CO2 ${\text{He}/\text{CO}}_{2}$ selectivity increases. [ 104 ] Overall, the investigated organosilica membrane demonstrates promising mixed gas behavior for separating permanent gases with small kinetic diameters from larger gas molecules. [ 104 ]…”
Section: Tuning Of Thin Film Barrier Properties and Permeabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Adjusting the permeability of plastics is an important task in many applications such as food or pharma packaging, membrane technology or water-sensitive OLED displays, and thus the subject of ongoing research activities [1][2][3]. Besides many other approaches, the plasma-enhanced deposition of thin film coatings stands out due to its versatility, low material usage and long-term stability [4].…”
Section: Introductionmentioning
confidence: 99%